Peningkatan Kompetensi Pedagogik Guru dalam Pembelajaran Jarak Jauh Melalui Pendampingan Sistem Daring, Luring, atau Kombinasi pada Masa New Normal Covid-19 - Ahmad Ahmad (Universitas Pendidikan Mandalika, 2020)
The purpose of this study was to improve the pedagogical competence of teachers in online, offline and combined distance learning in the Assisted Primary Schools of Segugus 05 Kopang, Central Lombok Regency. This research method used classroom action research. The data collection technique uses classroom observation techniques using the observation sheet instrument of teacher competency assessment in implementing distance learning programs (PJJ). The data analysis technique in this study used a comparative descriptive analysis technique. The results showed that PJJ with BDR (Learning From Home) with the Online, Offline or Combination system was able to improve teacher competence in learning. In Cycle-1, there was an increase in teacher competence in PJJ by 3.9%. However, this increase was successful when compared with the research success criteria with an increase of 5%. In Cycle-2, the increase in teacher competence in PJJ was 4.2%. In Cycle-3, the increase in teacher competence in PJJ was 14.1%. This study was successful because there was an increase in the research success criteria of 5%.